45 ACTIVATED PROTEIN C ATTENUATES THROMBIN-INDUCED BARRIER DYSFUNCTION IN HUMAN PULMONARY ARTERY ENDOTHELIAL CELLS VIA AN ENDOTHELIAL PROTEIN C RECEPTOR-DEPENDENT MECHANISM. (1st March 2005) - Finigan, J. H.; Dudek, S. M.; Singleton, P. A.; Chiang, E. T.; Camp, S. M.; Ye, S. Q.; Garcia, J. G.N.
Abstract : Rationale: Acute lung injury (ALI) is a frequent complication of sepsis in which disruption of the pulmonary endothelial cell (EC) monolayer leads to increased vascular permeability and life-threatening pulmonary edema. Activated protein C (APC) reduces mortality in sepsis; however, the mechanism through which it exerts its protective effect remains undefined. We hypothesized that APC, via interaction with the endothelial protein C receptor (EPCR), and the EC cytoskeletal protein phosphorylated myosin light chain (phosphoMLC), enhances EC barrier function. Methods: Transendothelial electrical resistance (TER) was measured in confluent human pulmonary artery EC monolayers cells treated with APC alone and with the addition of thrombin(0.2 U/mL). Activation of MLC via phosphorylation was assessed using Western blot analysis. Results: APC dose-dependently attenuated the thrombin-induced reductions in TER at 1 hr and Western blot analysis of APC (1 μg/mL)-challenged EC demonstrated a 3 fold increase in phosphoMLC (5 min) compared to control. Addition of an EPCR blocking antibody abolished APC-induced barrier-protection and increases in phosphoMLC, while incubation with a control antibody did not alter APC-mediated changes in TER or phosphoMLC levels. Incubation with an antibody against the thrombin receptor, PAR1, had no effect on APC-mediated increases in phosphoMLC. Conclusion: APC significantly reduces thrombin-induced barrier dysfunction in ECs via an EPCR-dependent mechanism. APC-mediated alterations in the cytoskeletal protein phosphoMLC was EPCR-dependent but independent of an interaction of APC with PAR1. Modulation of EC barrier function may play a crucial role in the improved survival in patients with sepsis and ALI treated with APC.